2015
DOI: 10.1021/cs501359n
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on the Mechanism of Homogeneous Catalytic Olefin Hydrogenation and Amine–Borane Dehydrogenation by a Versatile Boryl-Ligand-Based Cobalt Catalyst

Abstract: We have conducted mechanistic investigations using dispersion-corrected hybrid density functional theory on three different homogeneous processes: (a) hydrogenation of styrene using H2, (b) dehydrogenation of amine–borane, and (c) transfer hydrogenation of styrene using amine–borane catalyzed by a boryl-ligated Co-based catalytic system, LCo­(N2) (where L = meridional bis-phosphinoboryl (PBP) ligand), recently developed by Peters and co-workers (Lin, T.-P; Peters, J. C. J. Am. Chem. Soc. 2013, 135, 15310–15313… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 70 publications
0
54
0
1
Order By: Relevance
“…[23] It was suggested that carbond ioxide hydrogenation can be achieved using ap hotochemically renewable organohydrides, such as dihydropyridine. [27] Herein, we proposet hat catalytic dehydrogenation of chemisorbed hydrogens from B 24 N 24 H 32 could be achieved by the same active catalyst. Both of them turned out to be exoergic with reasonable barriers, which are likely to be surmountable at room temperature (see FiguresS7-S8 in the Supporting Information).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[23] It was suggested that carbond ioxide hydrogenation can be achieved using ap hotochemically renewable organohydrides, such as dihydropyridine. [27] Herein, we proposet hat catalytic dehydrogenation of chemisorbed hydrogens from B 24 N 24 H 32 could be achieved by the same active catalyst. Both of them turned out to be exoergic with reasonable barriers, which are likely to be surmountable at room temperature (see FiguresS7-S8 in the Supporting Information).…”
mentioning
confidence: 99%
“…Single-point solution-phase calculations were done using the CPCM model at B3PW91-D3/BS2l evel of theory and further tested at M06L-D3/BS2 level of theory (see Figure S10 in the Supporting Information). [27] For generation of LCo(H) 2 from LCo(H) 4 /LCo-N 2 ,p lease see [25,26] In the product (D_PDT1), the hydrideo nt he cobalt center is still weakly coordinated with the borona tom of the fullerene. It was theoretically shown that the terminal and bridging hydrogen of the active catalytic speciesL Co(H) 2 are negative and positive in nature, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Paul et al. studied the mechanism of two equivalent H 2 activations . In order to gain a general understanding about the LA‐TM‐catalyzed H 2 activation, we further systematically evaluated different H 2 activation modes (Figure ) mediated by PBP‐Co.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of the catalytic efficiency of the monomeric 7 and the dimeric complexes 8 showed a lower activity for the latter one. DFT calculations regarding the mechanism predicted the formation of ( t Bu PNBNP)Co(H) 2 as catalytic active species and the rate‐determining barrier for the hydrogenation of styrene of 17.3 kcal mol −1 …”
Section: Catalytic Reductionmentioning
confidence: 99%